Les populations autochtones de maïs au Mexique - Rafael Ortega Paczka (Revue d'ethnoécologie)
The article consists of three parts. In the first one, we address the peculiarities of maize crop more generally of the culture around maize in Mexico, in order to explain the need for in situ conservation and participatory improvement of this species. The second part mentions in very general terms, what has been done in research on the diversity of maize and the main trends and issues regarding the genetic improvement of the plant. In the third section, we expose and compare different aspects of participatory maize improvement in Mexico.